O FILHO DO HOMEM É SENHOR DO SÁBADO : MEMÓRIA E IDENTIDADE NOS EVANGELHOS SINÓTICOS - Carneiro, Marcelo da Silva (2014)
This research is about Memory and Identity in the Synoptic Gospels, in the view of Mk 2.23-28, Mt 12.1-8 and Lk 6.1-5, that read the conflict between Jesus and the Pharisees, about Plucking of the Grain on the Sabbath. We try the demonstrate that the Gospels narratives are indiciary of the communities identity that generate them, in the Greek-roman World, that orality and textuality has the same influence. Therefore, will study the colletive memory as oral tradition formative, as well the orality and textuality relation in Synoptic Gospels narratives and memories. The choice of the pericope is justified by the texts indicate a identity linked to Judaic culture, in that the Sabbath was a most important identity symbol of the Judaism of 1th Century. In this way the Protochristians communities has arguments to defend of accusations and in the same time define boundaries to insert their place in relation to other intrajudaic groups. Finally, in the elaboration of this document, each community choice a specific literary genre, closer to text purpose. In this way is possible identify which Gospel is closer to Judaic environment and which them is so far. In their narratives, the Evangelists want affirm whom is Jesus to the community as well, establishing his messianic identity. In the specific pericope, the most important logia is that affirm Jesus Son of Man as Lord of the Sabbath. Jesus assumes the community prototype, while the Pharisees, Jesus opponents, assume the role of their that dont have any concerned about the neighbor, try the justify themselves by the strict observance of the mosaic Law.